Subordinate Clause Analysis Found In Part III And IV “Gulliver’s Travels” Novel - Made Yuyun Bestari; Putu Devi Maharani; I Gusti Bagus Wahyu Nugraha Putra (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2021)
This study aims to find out the types of subordinate clause and the most occurring type of subordinate clause which found in Gulliver’s Travels Novel. The quantitative and qualitative method are applied to analysed the data which based on the theory from (Miller, 2002) and supported theory by (Kroeger, 2005). The study found that complement clause, relative clause, and adverbial clause were the types of subordinate clause found in this novel. The complementizers found in the complement clause namely that. In the relative clause, the conjunction found such as which, that, who, whose, whom, how, and Ø. Meanwhile, the conjunctions found in adverbial clause are before, where, when (time), as (manner), although (concession), and if, that (condition). There were total 35 sentences containing subordinate clause found in the novel such as 3 sentences (8,6%) of complement clause, 19 sentences (54,3%) of relative clause, and 13 sentences (37,1%). Therefore, the most occurring type of subordinate clause found in the novel is relative clause as subordinate clause with total 19 sentences (54,3%). Especially, the type of non-restrictive with 15 sentences found.